2015
DOI: 10.1007/s40618-015-0328-1
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate protects pancreatic beta cells against cytokine-induced damage via SIRT1 inhibiting NF-κB activation

Abstract: ART can elicit a protective effect on beta-cells exposed to IL-1β by stimulating SIRT1 expression, which resulted in the decrease of NF-κB activity, iNOS expression, and NO production. Hence, ART might be an effective drug for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…This was probably due to differences in mechanisms by which each ferroptosis inducer contributes to the various metabolic derangements that lead ultimately to ER stress. Since DFO has pleiotropic effects (inhibition of iron-mediated lipid peroxidation, inhibition of NF-κB activation, and involvement in several peroxidative systems [ 48 , 49 ]), DFO may affect ART-induced ER stress and its activation of NF-κB by preventing IκBα degradation [ 48 , 50 , 51 ]. Obviously, further studies are necessary to understand the molecular mechanism of differences between each ferroptosis inducer-induced ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to differences in mechanisms by which each ferroptosis inducer contributes to the various metabolic derangements that lead ultimately to ER stress. Since DFO has pleiotropic effects (inhibition of iron-mediated lipid peroxidation, inhibition of NF-κB activation, and involvement in several peroxidative systems [ 48 , 49 ]), DFO may affect ART-induced ER stress and its activation of NF-κB by preventing IκBα degradation [ 48 , 50 , 51 ]. Obviously, further studies are necessary to understand the molecular mechanism of differences between each ferroptosis inducer-induced ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed that artemether protected beta cells function by reducing the apoptosis of pancreatic beta cells and increasing insulin secretion in db/db mice. In cell experiments, artesunate was proved to protect pancreatic beta cells against cytokine-induced damage via SIRT1 inhibiting NF- κ B activation [ 22 ]. And in type 1 diabetic rat artemisinins as approved drugs were identified that can confer β cell characteristics to α cell.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes have more than double the risk of ICD after correction for other risk factors, relative to individuals without diabetes [68]. Yu et al newly found that artesunate could elicit a protective effect on pancreatic beta-cells exposed to IL-1 β by stimulating SIRT1 expression, which resulted in the decrease of NF-kB activity, iNOS expression, and NO production [69]. Hence, ART might be an effective drug for diabetes after ICD.…”
Section: Effect Of Artesunate On Central Nervous System Diseasesmentioning
confidence: 99%